Suppression of EZH2 inhibits TGF-β1-induced EMT in human retinal pigment epithelial cells. (September 2022) - Peng, Yu; Liao, Kai; Tan, Feng; Liang, Yuqin; Sun, Xihao; Cui, Zekai; Ye, Bo; Chen, Zhongping; Tang, Shibo; Chen, Jiansu
Abstract: Epithelial–mesenchymal transition (EMT) of retinal pigment epithelium (RPE) cells is critically involved in the occurrence of subretinal fibrosis. This study aimed to investigate the role of enhancer of zeste homolog 2 (EZH2) in EMT of human primary RPE cells and the underlying mechanisms of the anti-fibrotic effect of EZH2 suppression. Primary cultures of human RPE cells were treated with TGF-β1 for EMT induction. EZH2 was silenced by siRNA to assess the expression levels of epithelial and fibrotic markers using qRT-PCR, Western blot, and immunofluorescence staining assay. Furthermore, the cellular migration, proliferation and barrier function of RPE cells were evaluated. RNA-sequencing analyses were performed to investigate the underlying mechanisms of EZH2 inhibition. Herein, EZH2 silencing up-regulated epithelial marker ZO-1 and downregulated fibrotic ones including α-SMA, fibronectin, and collagen 1, alleviating EMT induced by TGF-β1 in RPE cells. Moreover, silencing EZH2 inhibited cellular migration and proliferation, but didn't affect cell apoptosis. Additionally, EZH2 suppression contributed to improved barrier functions after TGF-β1 stimulation. The results from RNA sequencing suggested that the anti-fibrotic effect of EZH2 inhibition was associated with the MAPK signaling pathway, cytokine-cytokine receptor interaction, and the TGF-beta signaling pathway. Our findings provide evidence that the suppression of EZH2 might reverse EMT and maintain the functions of RPE cells. EZH2 could be a potential therapeutic avenue for subretinal fibrosis. Highlights: 1. We demonstrated EZH2 inhibition could effectively alleviate the epithelial–mesenchymal transition induced by TGF-β1 and enhance the barrier function of human primary retinal pigment epithelial cells. 2. RNA-seq results indicated that the potential mechanisms may be related to the MAPK signaling pathway, cytokine-cytokine receptor interaction, and the TGF-β signaling pathway. 3. EZH2 could serve as a potential therapeutic target for subretinal fibrosis related to age-related macular degeneration or other retinal diseases.